ANALYSIS OF WATER AVAILABILITY LEVELS IN THE UPPER CITARUM RIVER BASIN - Alfiani, Latifah
The upstream Citarum watershed plays an important role in meeting the water needs of the Greater Bandung area, but there have been several records of drought events. Considering the population and water needs that continue to increase, a study is needed to evaluate water availability, this study aims to determine the per capita water availability index in each of the upstream Citarum Sub-watersheds in 2020-2099 and is divided into four periods. The data used are rainfall projections, temperature projections, land use maps of the Upper Citarum watershed and population data. The population projection method chosen is the logarithmic method. The runoff discharge was estimated by the Thorthwaite-Mather method. Furthermore, the mainstay debit calculation is carried out for a period of 20 years. The mainstay debit is divided by the projected population to get a per capita water availability index. The results obtained in the first period that the northern part of the upstream Citarum watershed is included in the absolute scarcity category, while